The Impact of Digital Infrastructure on African Development - Calderon, Cesar; Cantu, Catalina (World Bank, Washington, DC, 2021)
This paper estimates the impact of digital infrastructure on economic growth and its sources. The analysis uses system generalized method of moments and finds evidence of a causal impact from the digital infrastructure variables to economic growth, its sources, income inequality, and poverty. The findings show that mobile connections have an impact on economic growth through the total factor productivity growth channel, while internet users drive it by the capital accumulation channel. Connections have a negative effect on the Gini coefficient, and internet users have a negative effect on the poverty headcount. The analysis also finds that human capital and access to electricity are important complementarities for digital infrastructure to reap benefits. There would be large economic gains if Africa were to close the digital infrastructure gap relative to other regions, yet there are some issues of affordability and skills that need to be addressed to reduce the usage gap and the digital divide across gender, rural-urban, and firm size.